Clinical and Psychometric Evaluations of the Cerebral Vision Screening Questionnaire in 461 Nonaphasic Individuals Poststroke. (March 2016) - Neumann, Guenter; Schaadt, Anna-Katharina; Reinhart, Stefan; Kerkhoff, Georg
Background . Cerebral vision disorders (CVDs) are frequent after brain damage and impair the patient's outcome. Yet clinically and psychometrically validated procedures for the anamnesis of CVD are lacking. Objective . To evaluate the clinical validity and psychometric qualities of the Cerebral Vision Screening Questionnaire (CVSQ) for the anamnesis of CVD in individuals poststroke. Methods . Analysis of the patients' subjective visual complaints in the 10-item CVSQ in relation to objective visual perimetry, tests of reading, visual scanning, visual acuity, spatial contrast sensitivity, light/dark adaptation, and visual depth judgments. Psychometric analyses of concurrent validity, specificity, sensitivity, positive/negative predictive value, and interrater reliability were also done. Results . Four hundred sixty-one patients with unilateral (39.5% left, 47.5% right) or bilateral stroke (13.0%) were included. Most patients were assessed in the chronic stage, on average 36.7 (range = 1-620) weeks poststroke. The majority of all patients (96.4%) recognized their visual symptoms within 1 week poststroke when asked for specifically. Mean concurrent validity of the CVSQ with objective tests was 0.64 (0.54-0.79, P < .05). The mean positive predictive value was 80.1%, mean negative predictive value 82.9%, mean specificity 81.7%, and mean sensitivity 79.8%. The mean interrater reliability was 0.76 for a 1-week interval between both assessments (all P < .05). Conclusion . The CVSQ is suitable for the anamnesis of CVD poststroke because of its brevity (10 minute), clinical validity, and good psychometric qualities. It, thus, improves neurovisual diagnosis and guides the clinician in the selection of necessary assessments and appropriate neurovisual therapies for the patient.